Transformational Leadership Style in Implementing Madrasa Based Management - Aat Royhatudin; Supardi Supardi; Juhji Juhji (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2020)
The purpose of writing this article is to find out the transformational leadership style and how the implementation of Madrasa-based Management at Madrasa Tsanawiyah Annizhomiyah with its transformational leadership style. This research used a descriptive qualitative approach. Data collection was obtained from informants and the behavior of people who were observed, interviewed, and documented as the primary data sources and the rest was secondary data from available documents. The results of this study show that the Madrasa principal's transformational leadership style looks innovative, committed, and communicative and appreciates achievement, able to create a conducive atmosphere by making efforts to change awareness, inspiring teachers and staff to work together to become good team-work. Principal’s transformational leadership style at Madrasa Tsanawiyah Annizhomiyah includes curriculum management, student and teacher management, financial management and finance, infrastructure management, public relations management, and special service management can run optimally by the school vision, community needs, and jihad resolution spirit and high commitment built by teachers to build Madrasa education, wiling to improve quality of education, and positive thinking because every student can be a better person.